2022
DOI: 10.3390/jcm11185263
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Double-Blind Crossover Study for Evaluating a Probiotic Mixture on Gastrointestinal and Behavioral Symptoms of Autistic Children

Abstract: Autism spectrum disorders (ASDs) represent a diagnostic challenge with a still partially uncertain etiology, in which genetic and environmental factors have now been assessed. Among the hypotheses underlying the involvement of biological and environmental factors, the gut–brain axis is of particular interest in autism spectrum disorders. Several studies have highlighted the related incidence of particular gastrointestinal symptoms (GISs) in children suffering from ASDs. Probiotics have shown success in treatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 76 publications
0
8
0
Order By: Relevance
“…perceived), with the administration of these specific probiotics: Streptococcus thermophilus, Bifidobacterium longum, Limosilactobacillus fermentum and Ligilactobacillus salivarius. The presence of these taxa related to the cited species was present in fecal samples, indicating intestinal colonization by probiotics in these patients (Guidetti et al, 2022).…”
Section: Gut-brain Relationship In Children With Asdmentioning
confidence: 82%
“…perceived), with the administration of these specific probiotics: Streptococcus thermophilus, Bifidobacterium longum, Limosilactobacillus fermentum and Ligilactobacillus salivarius. The presence of these taxa related to the cited species was present in fecal samples, indicating intestinal colonization by probiotics in these patients (Guidetti et al, 2022).…”
Section: Gut-brain Relationship In Children With Asdmentioning
confidence: 82%
“…Although clinical trial findings are limited, they urge additional investigation into FMT in ASD. This scoping review found that probiotic, prebiotic, synbiotic, FMT, or MTT supplementation improved different domains of ATEC score, including sociability, sensory or cognitive awareness, speech/communication/language, and health/physical/behavior, and there were improvements in behavioral symptoms in other studies that used different questionnaires (not ATEC) [ 29 , 45 , 46 , 47 , 48 , 50 , 52 , 54 , 55 , 57 , 58 ]. Concerning GI symptoms, all of the included trials found that probiotic, prebiotic, or symbiotic treatment improved the frequency of bowel movement-associated pain, diarrhea, constipation, and stool frequency [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Bifidobacteria levels appear to be inversely associated via feedback interactions with Desulfovibrio and Clostridium , two of the most likely bacteria strains involved in ASD etiopathogenesis [ 84 ]. In this vein, our analysis suggests that when baseline counts are aberrant, enhancing Bifidobacterial populations (MTT, B-GOS ® supplementation) or reducing Desulfovibrio and Clostridium growth rates might be viable targets in microbiota-based ASD therapy [ 46 , 47 , 48 , 49 , 50 , 51 , 52 ]. It is critical to understand which gut commensals are associated with better symptoms in order to generate next-generation probiotics (also known as live biotherapeutic products) that evolve the features required to complete within the GI tract of ASD patients [ 85 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although no significant differences were observed in microbiome alpha diversity among groups, beta diversity in children with ASD were significantly different between start and at 3 months compared to those without ASD. There were some taxa that were positively associated with the three-month samples, such as Bifidobacterium longum , Streptococcus thermophilus , Limosilactobacillus fermentum , and Ligilactobacillus salivarius [ 162 ].…”
Section: Gut Microbiota In Children and Adolescents With Asdmentioning
confidence: 99%